2021
DOI: 10.1021/acs.molpharmaceut.0c00696
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Microparticles Encapsulated with Diallyl Trisulfide Interfere with the Inflammatory Tumor Microenvironment and Lung Metastasis of Invasive Melanoma

Abstract: Lung metastasis is a fatal and late-stage event for many solid tumors. Multiple lines of evidence have demonstrated that diallyl trisulfide (DATS), an active ingredient of garlic, possesses striking antimetastatic effects. However, the lack of highly efficient organ-compatible carriers restricts its application. In the present study, we showed that extracellular microparticles encapsulated with DATS (DATS-MPs) were capable of interfering with the prometastatic inflammatory microenvironment in local tissues. DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…lial cells were able to uptake MPs, initiate an inflammatory response, and promote the formation of PMN(Liu et al, 2021). In the present study, we found that 10 μg/ml of MPs could induce both MLE-12 andMH-S cells to secret critical inflammatory factors including MCP-1.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…lial cells were able to uptake MPs, initiate an inflammatory response, and promote the formation of PMN(Liu et al, 2021). In the present study, we found that 10 μg/ml of MPs could induce both MLE-12 andMH-S cells to secret critical inflammatory factors including MCP-1.…”
supporting
confidence: 54%
“…It has been held that lung tissue is rich in alveoli, which are mainly composed of macrophages and epithelial cells (Altorki et al, 2019). Previous studies showed that both lung macrophages and lung epithelial cells were able to uptake MPs, initiate an inflammatory response, and promote the formation of PMN (Liu et al, 2021). In the present study, we found that 10 μg/ml of MPs could induce both MLE‐12 and MH‐S cells to secret critical inflammatory factors including MCP‐1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result showed that the heterogeneity was not driven by a single study. However, after the removal of Liu et al 76 (Figure 5) and Pan et al 85 (Figure 7b), the heterogeneity was reduced to 41% and 27% for cancer metastasis and targeting.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 97%